Potential Advantages of Peroxoborates and Their Ester Adducts Over Hydrogen Peroxide as Therapeutic Agents in Oral Healthcare Products: Chemical/Biochemical Reactivity Considerations In Vitro, Ex Vivo And In Vivo - Martin Grootveld; Edward Lynch; Georgina Page; Wyman Chan; Benita Percival; Eugenia Anagnostaki; Valina Mylona; Sonia Bordin-Aykroyd; Kerry L. Grootveld (MDPI AG, 2020)
Peroxides present in oral healthcare products generally exert favourable protective activities against the development and progression of tooth decay, plaque, gingivitis, and halitosis, etc. However, despite the high level of research focus on hydrogen and carbamide peroxides as therapeutically active (and tooth-whitening) agents, to date the use of alternative chemical forms of peroxides such as peroxoborates for these purposes has received only scant attention. Intriguingly, peroxoborate and its esters with polyols, such as glycerol, have a very diverse chemistry/biochemistry in aqueous solution, for which there is an increasing amount of evidence that it remains distinctive from that of hydrogen peroxide; such properties include self-associative and hydrolytic equilibria, and their abilities to participate in electrophile- or nucleophile-scavenging, metal ion-complexing, redox and free radical reactions, for example. Therefore, the purpose of this detailed commentary is to evaluate both differences and similarities between the molecular/biomolecular reactivities of peroxoborate species and hydrogen peroxide in vitro, ex-vivo and in vivo. It encompasses brief sectional accounts regarding the molecular heterogeneity of peroxoborates, the release of bioactive agents therefrom, and their oxidative attack on oral cavity biomolecules (the nucleophilic or electrophilic character of these oxidations are discussed). Further areas explored are the abilities of borates and peroxoborates to enhance the solubility of iron ions in aqueous solution, their involvements in free radical biochemistry (particularly the complexation of oxygen radical-promoting transition metal ions by, and antioxidant properties of, peroxoborate-polyol ester adducts), and the specific inhibition of protease enzymes. Further aspects focus on the tooth-whitening, oral malodor neutralizing, and potential mutagenic and genotoxic properties of peroxoborates, along with possible mechanisms for these processes. The abilities of peroxoborates, and peroxides in general, to modulate the activities of inflammatory mediators and vitamins, antioxidant or otherwise, are also explored.